EXPLORATION OF WATER DROP AS A EVENT DIGITAL STILL LIFE PHOTOGRAPHY WORKS WITH Symmetrical COMPOSITION - Martinus Eko Prasetyo (Titik Imaji, 2022)
Advances in digital technology have an influence on the world of photography, many general public have started to study photography as an embodiment of hobbies and creative expressions. Expression photography is an expression of the soul that prioritizes the expression of one's personal identity which will be expressed in a work of pure art. That photography is able to stand as a work of art because of the expression of meaning and part of the expression of work that is done by humans in this case as a photographer. Art photography is a photo that is a reflection of the soul, emotions of the photographer. Of course, the research emphasizes that it is important to express in your work but don't forget to apply a conceptual mindset and at least apply methods in the creation of photographic works as a basis for thinking so that the work can be strong in message and meaning. One genre of photography that can realize an expression is Water Drop photography using the freeze photography technique. The form of visual references as ideas in a visual water drop will resemble the imagination of the photographer in conveying a message to the audience, this is one of the beauty of the graphic art of water drop photography. Starting from the development of ideas that are trying to appear in the form of visual photography based on water splash photography references in previous research conducted by Syafriyandi in a study entitled SENSATION OF COLOR SPLASH IN EXPRESSION PHOTOGRAPHY WORKS. This research concludes that water drop photography is not only the embodiment of artistic expression, but can be explored into a beautiful form of graphic art that is desired as an embodiment of ideas and can even be arranged from the placement of composition as an emphasis on photography.